IMPROVEMENT OF RELATIONS BETWEEN THE LOCAL COUNCIL AND EXECUTIVE BODIES IN THE ECONOMIC DEVELOPMENT OF REGIONS - Bekchanov Davron Masharipovich (Scholar Express Journals, 2024)
This article reveals organizational and legal problems in the interaction of local representation and executive bodies in the economic development of regions, and provides suggestions on the relevant legislation of the Republic of Uzbekistan and the improvement of the activities of local state authorities.
Keywords: region; economic development; local council; non-governmental organizations